Economic and Social Survey of Asia and the Pacific 1999 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 1999)
This year's issue of the survey reviews the economic progress in the ESCAP region over the past year and analyzes population dynamics and their related policy implications. It also provides a regional perspective on the subject of 'Financing for Development' looking at such issues as: domestic and external resources; trends in and current distribution of Official Development Assistance; and reform of the international financial architecture.